Mills' Behavior of Prices - Viner, Jacob; Mills, Frederick (Quarterly Journal of Economics, 1929)
Journal Article Mills' Behavior of Prices Get access Jacob Viner Jacob Viner University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 2, February 1929, Pages 337–352, https://doi.org/10.2307/1882477 Published: 01 February 1929